Mantle Cell Lymphoma Mimicking as Irreducible Inguinal Hernia – A Rare Case Report: Life Sciences -General surgery - Barathiraja, Dr.; M, Dr.Jayasurya; Sasi Kumar, Dr.; Karthikeyan, Dr.; J, Dr.Thanka (International Journal of Life Science and Pharma Research, 2023)
Lymphomas are malignant neoplasms originating from bone marrow and lymphatic structures resulting in the proliferation of lymphocytes. It is divided into Hodgkin’s and Non-Hodgkin’s lymphoma. Among Non-Hodgkin’s lymphoma, diffuse large B cell type is the most common, and the follicular variant is next. Mantle cell lymphoma (MCL) is one of the least common varieties of Non-Hodgkin’s lymphoma. It is a case of mantle cell lymphoma presented as an irreducible inguinal hernia. This case report aims to tell us that when it comes to inguinal hernias, most of them do not concentrate on general examination. In this case, it's clear that even if a patient present with an inguinal hernia, it is mandatory to rule out other common clinical findings to prevent misdiagnosis. Even though previous similar cases described were of lymphomas identified in the hernia sac along with the hernia component, it is the first report of mantle cell lymphoma, which presented as an inguinal swelling mimicking an irreducible inguinal hernia. This 72-year male patient, a farmer by occupation, complained of swelling and pain over the right groin. On examination, we found multiple enlarged inguinal lymph nodes raised the suspicion of lymphoma. We proceeded with a CT abdomen and chest, followed by surgery, and mantle cell lymphoma was diagnosed after immunohistochemistry results. The patient was referred for chemotherapy, and a long-term follow-up was done. The patient was doing good. Furthermore, it highlights the significance of the role played by surgeons in screening by sending only macroscopically unusual specimens for microscopic analysis. Here, we present a case of primary non-lymphoma Hodgkin's of the sigmoid colon that manifested as an inguinal hernia that was completely irreducible.